The ecosystem approach to marine management in the Arctic: Opportunities and challenges for integration - Wienrich, Nicole; Buschman, Victoria Qutuuq; Coon, Catherine; Fuller, Susanna; Hennicke, Janos; Humrich, Christoph; Prip, Christian; Wenzel, Lauren (Frontiers in Marine Science, 2022)
Climate change is strongly impacting Arctic marine ecosystems, and the Arctic coastal communities whose identities, traditions and livelihoods are closely interconnected with the marine environment. The Ecosystem Approach (EA) is a promising approach for understanding and managing the occurring shifts in the Arctic marine ecosystems. Based on our analysis, we find that assessments conducted by international and regional instruments and institutions, most notably the Arctic Council, as well as the wealth of Indigenous knowledge present in the region, provide valuable starting points for the implementation of EA in the Arctic. Yet, mechanisms for translating knowledge into joint coordinated and integrated action in accordance with EA are currently lacking. Our analysis suggests that incremental steps can be taken now to promote the implementation of EA, while working to establish a more comprehensive governance framework. In our view, bottom-up initiatives may provide the most promising avenue for promoting the application of EA in the region under the current geopolitical circumstances. Support by civil society, Indigenous and conservation organizations, as well as global momentum will be necessary to coordinate, finance and elevate community-driven initiatives. Other opportunities we identify for advancing EA is to engage with sectoral management bodies and to advance EA through climate change adaptation measures